Recent research and progress of biodegradable zinc alloys and composites for biomedical applications: Biomechanical and biocorrosion perspectives - Humayun Kabir; Khurram Munir; Cuie Wen; Yuncang Li (Bioactive Materials, 2021)
Biodegradable metals (BMs) gradually degrade in vivo by releasing corrosion products once exposed to the physiological environment in the body. Complete dissolution of biodegradable implants assists tissue healing, with no implant residues in the surrounding tissues. In recent years, three classes of BMs have been extensively investigated, including magnesium (Mg)-based, iron (Fe)-based, and zinc (Zn)-based BMs. Among these three BMs, Mg-based materials have undergone the most clinical trials. However, Mg-based BMs generally exhibit faster degradation rates, which may not match the healing periods for bone tissue, whereas Fe-based BMs exhibit slower and less complete in vivo degradation. Zn-based BMs are now considered a new class of BMs due to their intermediate degradation rates, which fall between those of Mg-based BMs and Fe-based BMs, thus requiring extensive research to validate their suitability for biomedical applications. In the present study, recent research and development on Zn-based BMs are reviewed in conjunction with discussion of their advantages and limitations in relation to existing BMs. The underlying roles of alloy composition, microstructure, and processing technique on the mechanical and corrosion properties of Zn-based BMs are also discussed.